Mothman's curse - Hayes, Christine, 1972- (Roaring Brook Press, 2015)
"When Josie and her brother Fox discover the truth behind the legend of the Mothman, they must stop a disaster in order to break the curse that has been afflicting their town"--Provided by publisher.